Pendidikan Keluarga Seimbang yang Melekat Sebagai Basis yang Mencerahkan Anak di Era Digital - Azam Syukur Rahmatullah (Cendekia: Kependidikan dan Kemasyarakatan, 2017)
The degree of behavioral deviation done by children in the present era is increasingly apprehensive, especially in the digital era which anything seems sophisticated resulting children are "spoiled and pampered" by technological prowess. This is what is called a "digital trap”, and one of the things that makes it easy for children to get into the trap is due to the "Split Personality" between a child and a parent. In the absence of pure relation and attachment between a child and a parent, consequently, the parent's obligation to the child is not fulfilled, one of which is a sincere accompaniment to a child when she or he explores the virtual world through digital media. Therefore, it becomes important that balanced family education is inherent with the child in the home, so that parents more easily lead the child into the positive way while browsing the virtual world through digital media. The parenting patternsought to beapplied based on a strong godliness, open and not manipulative.إن نسبة انحراف السلوكيات التي قام بها الأطفال في هذا العصر يثير المخاوف. وخاصة في هذا العصر (العصر الرقمي) بما فيه من الأشياء الراقية، جعل الأولاد مُدلّلين فيه بتقدم التقنية. وهذا هو المسمّى بالفخاخ الرقمي، وأحد الأسباب في سهولة الأطفال للدخول في الفخاخ الرقمي هو وجود  انفصام الشخصية بين الأولاد والوالدين. وبعدم القرب الخالص بين الأولاد والوالدين لا يستقيم أداء واجبات الوالدين تجاه الأولاد، ومنها مصاحبة خالصة نحو الأبناء حين غاصوا في الفضاء الإلكتروني عن طريق الجهاز الرقمي، لذا فإن التربية الأسرية المتّزنة مهمة للأولاد في البيت، ليسهل للآباء توجيه الأولاد إلى الطريق السويّ الإيجابيّ طوال غوص هؤلاء في الفضاء الإلكتروني. وأسلوب تحضين الأولاد الذي يمكن للوالدين اتّخاذه هو الأسلوب القويّ المؤسّس على الدين، والمتفتّح ولا خداع فيه.